The Knowledge and Attitude of Nurses as an Efforts to Prevent Covid-19 - Solihuddin Harahap; Sri Hernawati Sirait; Lestari Lestari; Nita Andriani Lubis (Health Notions, 2022)
Background: Coronaviruses are a large family of viruses that are transmitted zoonically (between animals and humans) and can cause mild to severe symptoms. SARS-CoV-2 infection in humans causes symptoms of acute respiratory distress such as fever, cough, and shortness of breath. In severe cases, the disease can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. Efforts to break the chain of spread of COVID-19 require a good understanding and knowledge of all elements including nurses. Objective: To find similarities, advantages, and disadvantages regarding the Description of Nurses' Knowledge and Attitudes to prevent Covid-19 disease in 2021. Methods: This study used a descriptive type with a Literature review design obtained from sources from the International Journal of Nursing Research (IJNR) and the National Library. The keywords in this study were Description, Knowledge, Attitudes, Nurses, Covid-19 Prevention. Results: From five articles on the Description of Nurses' Knowledge and Attitudes to prevent Covid-19 disease, four articles had good knowledge and attitudes and there was one article which stated that nurses' knowledge and attitudes were still not good. Conclusion: This study aims to determine the similarities, advantages, and disadvantages of using a literature review. Of the five articles, it shows that the five research journals have research similarities in this research method, the five journals use descriptive research methods, there are 4 journals that have similarities in the sample, namely nurses, the third equation there are five journals that use a cross sectional approach. The advantages of this study are that there are four complete studies in accordance with the research objectives, and the drawback of this research is that there is one incomplete article whose research is not in accordance with its objectives. Keywords: knowledge; attitude; nurse; Covid-19 prevention